Early Diagnosis and Intervention in Cystic Fibrosis: Imagining the Unimaginable - Coverstone, Andrea M.; Ferkol, Thomas W. (Frontiers in Pediatrics, 2021)
Cystic fibrosis is the most common life-shortening genetic disease affecting Caucasians, clinically manifested by fat malabsorption, poor growth and nutrition, and recurrent sinopulmonary infections. Newborn screening programs for cystic fibrosis are now implemented throughout the United States and in many nations worldwide. Early diagnosis and interventions have led to improved clinical outcomes for people with cystic fibrosis. Newer cystic fibrosis transmembrane conductance regulator (CFTR) potentiators and correctors with mutation-specific effects have increasingly been used in children, and these agents are revolutionizing care. Indeed, it is possible that highly effective modulator therapy used early in life could profoundly affect the trajectory of cystic fibrosis lung disease, and primary prevention may be achievable.